Silicon self - assembled nanodots fabricated using a radio - frequency magnetron sputtering method [electronic resource] - 398612 Lim, Qiao Jie; Samsudi Sakrani, supervisor; Yusof Wahab, supervisor; Fakulti Sains (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2008